The wisdom of F. La Rochefoucauld’s in the book «Maxims and moral reﬂections» - Rubanau, Anatoly V. (Journal of the Belarusian State University. Philosophy and Psychology, 2024)
The views of F. La Rochefoucauld are considered, according to which human life is the result of the interaction of fate, chance, on the one hand, and will, human actions, on the other. It is noted that passions guide behaviour and determine the mood of people. The inﬂuence of passions is stronger than the inﬂuence of reason. The ability of a person to know the world of his passions, master them and even hide them from others is very limited. One of the strongest human passions is pride. Pride sets in motion both virtues and vices. Analysing the tactics of human actions, F. La Rochefoucauld subjects them to a versatile critical analysis, points out the need for greater objectivity and self-criticism of people in relation to themselves. Positive traits of character are highlighted: fearlessness, generosity, kindness and sincerity.
Keywords: personality; behaviour; passions; intelligence; character; self love; virtues; vices